Teacher Perceptions of the Instructional Leadership Practices of Principals - Don Leech; James L. Pate; Nicole M. Gibson; Ronny Green; Robert Smith (School Leadership Review, 2009)
In today’s world school leadership, particularly instructional leadership, has taken on a new look. The era of high- stakes accountability has changed almost everything. The instructional leader of the 80’s was presented as an efficient top-down, task oriented manager who was focused on curriculum and instruction rather than buildings and budgets (Lashway, 2002). Gone are the days when principals spent most of their time with bus schedules, fire drills, and general curriculum, says the National Association of Elementary Principals (Henry, 2001). Leaders must keep abreast of state and federal goals, the latest technologies and teaching practices, as well as learn to use data to identify learning gaps among all students.